The Responsibility of the Notary in Providing Legal Information to the Parties on the Deed He Made - Chilsy Indiyarti; Sri Kusriyah; Peni Rinda Listyawati (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
Legal Counseling is carried out by providing clear, directed explanations, so that the meaning and purpose of the authentic deed are easily understood and understood by the parties. Sometimes people only provide explanations and documents without knowing the legal issues. Article 15 paragraph paragraph 2 letter e of Act No. 2 of 2014 explains that,